Factors influencing gender preference for child among married women attending ante-natal clinic in a tertiary care hospital in Delhi: a cross sectional study - Chellaiyan, Vinoth Gnana; Adhikary, Mrinmoy; Das, Timiresh Kumar; Taneja, Neha; Daral, Shailaja (International Journal Of Community Medicine And Public Health, 2018)
Background: Gender discrimination is the unfair denial of opportunities and violation of their rights. Despite of discrimination laws and regulations, women are subjected to unequal treatment in all the phases of their life in India. The present study was conducted among antenatal women to determine their preference, if any, for male child and their awareness regarding technology and legality for sex determination of fetus in a tertiary care hospital. Methods: The study was a cross sectional study conducted among pregnant women aged 18 years and above attending antenatal clinic at Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi from June 2015- May 2016. Systematic random sampling method was used to include 238 study participants. A pre-tested, semi-structured, and self-administered questionnaire was used. Data was analyzed using SPSS v.21.0. Chi-square test was applied to test significance of difference (p˂0.05). Results: Among 238 study participants, mean age of study participants was 29 (±3.5) years. About 107 (45.0%) pregnant women had no gender preference. 88 (37%) preferred male child, the major reasons quoted for male child preference were pressure from family 29 (32.95%) and social responsibilities carried by male 25 (28.40%). Only 43 (18.0%) women preferred a female child. 187 (78.57%) study participants, were aware regarding sex determination and 72 (30.25%) said private hospital preferred place for sex determination. 36.56% women had knowledge about the legal implications associated with sex determination. Conclusions: The present study showed the high existence of male preference in our society which is a common barrier in achieving reduced national fertility levels. So, there is every need to bring about changes in social, economic, and political structure in order to reduce gender inequality in India.